Reversible Rapid Neck Swelling Following Carotid Artery Stenting: A Case Report - Shyamkumar N. Keshava; Thomas Mammen; Edwin Stephen; Sunil Agarwal (Journal of Clinical Interventional Radiology ISVIR)
We report a case of rapid neck swelling from diffuse enlargement of the parotid gland that developed following stenting of the common carotid artery for significant stenosis in a postradiation scenario. Hyperperfusion was considered as the possible mechanism. The pathology and differential diagnoses are discussed. It was conservatively managed and there was significant reduction in the swelling within three days.